Optimalisasi Keterampilan Menulis Teks Pidato Melalui Pendekatan Pemberian Tugas di SMP - Nurharyanti, Farida (Manajemen Pendidikan, 2015)
This research  aim to description  about improvement  of achievement  of matter learning skill reads textbook through giving approach of duty. Subject and research data source 20 students. Data collecting method applies observation, documentation,  and test. Data  analysis  applies  critical  analysis  and  comparability.   Indicator  success  of  using minimal limit criteria 75 and complete target of 100%. Research procedure applies cycle. Result of research and solution as follows : data obtained from finite precycle of cycle II, obtained progress of achievement of student learning in study of Indonesian with matter skill reads textbook,  at precycle average of 71,7 and cycle I average of 75,1 and cycle II average  of 85,1. From this data, seems to explain  that happened  increase  of average  of value  from  precycle  to cycle  I 3,4 numbers  (4,7%),  from  cycle  I to cycle  II happened increase 10 numbers (13,3%), from precycle to cycle II happened increase 13,4 numbers (18,7%).  Highest  value of phase precycle  82 and cycle I 86 and cycle II 92. Seems  to explain that from phase precycle to cycle I happened increase equal to 4 number (4,9%), from cycle I to cycle II happened increase equal to 6 number (7%), and from precycle to cycle II happened increase 10 numbers (12,2%). Low value of phase precycle is obtained [by] 64 and cycle I 68 and cycle II 76. thereby, can be affirmed that from phase precycle to cycle I happened  increase  equal to 4 number  (6,3%),  from cycle I to cycle II happened increase equal to 8 number (11,8%), and from precycle to cycle II happened increase 12 numbers  (18,8%).  Complete  percentage  learnt starts from precycle  is obtained  equal to25% and cycle I is obtained equal to 50% and cycle II equal to 100%. Seems to explainthat from phase precycle to cycle I happened increase equal to 25%, from cycle I to cycle IIhappened increase equal to 50%, and from precycle to cycle II happened increase equal to75%. Thereby, achievement  of student learning in study of Indonesian with matter skill reads textbook from finite precycle of cycle II happened increase significant.